Firm Performance and Market Behavior during First Wave of COVID-19 in Egypt: Panel Data Analysis - May Elewa; Shwikar Nagy (Asian Journal of Finance & Accounting, 2024)
The purpose of this paper is to identify the impact of market capital MC and net profit NP on stock price SP and trade volume (TV) in the developing Egyptian business context. This study collects data from 29 non-financial organizations registered on the EGX 30 during the 6 month, 1/1/2020 to 30/6/2020, lockdown in Egypt due to the first wave of COVID-19. Data for the monthly confirmed cases and death cases of COVID-19 are collected for the 6 months of the study and compared to the monthly records of closing prices and trade volume in Egyptian pounds EGP. The study population represents 174 firm year observations. The firms studied operate in cash, have annual financial reports during the period 1/1 to 31/12, obtain complete financial data, and have not been eliminated all throughout the study. In this work the pooled model, the fixed effects model, and the random effects model are used. SPSS is applied to achieve the required statistical analysis. The study is a panel data analysis. Outcomes demonstrate existing substantial effects between market capital MC and stock price SP during the first wave of COVID-19. However, no significant effect is evident of the market capital MC and net profit NP with the trade volume TV during the first wave of this pandemic. This literature is advantageous for external and internal stakeholders and regulatory bodies. The study is a modest contribution that may help boost the business processes to reach better financial performance in times of unexpected catastrophes.